2018
DOI: 10.1111/jora.12393
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Group Differences in Bullying Perpetration: A Meta‐Analysis

Abstract: We examined ethnic differences in bullying perpetration in order to assess whether ethnic group membership was associated with higher involvement among (1) nonimmigrant and immigrant youth; and (2) White and visible minority youth (i.e., Black, Hispanic, Asian, Indigenous, and Biracial). Fifty-three studies (N = 740,176; 6-18-year-olds) were included in the meta-analysis. Results yielded very small and nonsignificant effect size differences across all group comparisons. Methodological moderator analyses indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 117 publications
1
31
0
Order By: Relevance
“…Although the great diversity in the types of harassment makes it impossible to determine a specific profile [8], the review of the literature has shown that ethnic minorities are prone to suffer this type of violence [17], especially among first generation migrants [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the great diversity in the types of harassment makes it impossible to determine a specific profile [8], the review of the literature has shown that ethnic minorities are prone to suffer this type of violence [17], especially among first generation migrants [18].…”
Section: Discussionmentioning
confidence: 99%
“…As with certain minorities, ethnic minorities are prone to being harassment victims [16], more so for first-generation immigrants than second-generation ones [17]. It is difficult to determine group differences in harassment actions [18]. There are factors such as ethnic identity that do have a direct influence [19], and even other factors such as the existence of low or very low socio-economic and cultural status [20].…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between ethnic/migration background and bullying is not clear. Two recent meta‐analyses showed large between‐study heterogeneity 44,45 . This may partly be explained by an important aspect in the process of bullying, namely that bullies single out victims as being different, 43 and what constitutes being different may vary in relation to the degree of homogeneity or heterogeneity of social circumstances in a given school setting.…”
Section: The Importance Of Individual Social Characteristicsmentioning
confidence: 99%
“…Previous studies have argued for differentiating between various ethnic groups in studying peer relationships and processes (Bikmen 2011;Vitoroulis and Vaillancourt 2018). By investigating two specific ethnic groups and not combining multiple immigrant groups, this study aimed to take into account the possibility that processes of friendship and rejection differ between ethnic groups.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…In the context of ethnically diverse classrooms, interethnic aggression may be perceived as behavior that reinforces ethnic boundaries. Previous research has shown that although ethnic groups might slightly differ in the extent to which they behave aggressively, same-and cross-ethnic aggression was equally common (Tolsma et al 2013;Vitoroulis and Vaillancourt 2018). Whereas this suggests that adolescents' aggressive behavior in itself may not highlight ethnic boundaries, it remains unclear how classmates respond to adolescents' same-and cross-ethnic aggression and, consequently, whether aggressive behavior might indirectly affect ethnic boundaries in classrooms.…”
Section: Introductionmentioning
confidence: 95%